Designing of Goat’s Food Processing Tools Using Quality Function Deployment Method - Isana Arum Primasari; Hapsoro Agung Jatmiko; Edo Rizki Drianbodo; Oldy Riswan (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
Goat, is one of the most consume meat in Indonesia, it provides much nutrition to the eater and highly recommended by several nutritionist. One of the most critical part in breeding goats, is feeding them, this process is one of the most time consuming and takes a lot of effort, as the food preparation requires a lot of item to mix. Breeder, nowadays mostly feed their goat with “dry food” which are mostly consist of concentrate, this process unfortunately still done manually which, not only takes time but also some chances of potential hazard because most of the concentrate are heavy and huge. This research takes place in Rejodani District in Sleman Regency thus the sample and population of the research are goat breeder around the area. Using Quality Function Deployment method, authors intended to create a new food processing tools for food preparation of the goats. Using the concept screening and selection, out of 3 proposed design, the best design is chosen, followed by validation process to the respondents of the research. The final design of the food processor is the one that could increase productivity of the breeder and less chance of hazard.